Muhammad's Body : Baraka Networks and the Prophetic Assemblage - Knight, Michael Muhammad (Islamic civilization & Muslim networks., 2020)
"Knight approaches hadith and sira as important religio-cultural and literary phenomena in their own right. In rich detail, he lays out the immense variety of questions and depictions early followers produced regarding Muhammad's sacred power (baraka)-its boundaries, effects, and limits. Drawing on insights from contemporary theory about the body, he shows how changing representations of the Prophet's body helped to legitimatize certain types of people or individuals as religious authorities, while marginalizing or delegitimizing others. For some Sunni Muslims, Knight concludes, claims of religious authority today continue to be connected to ideas about Muhammad's body"--